Wischnewski spots in a case of accidental hypothermia. Issue 8 (6th May 2021) - Flabouris, Katerina; Russell, Patrick; Wills, Stephen
Abstract: Accidental hypothermia can be fatal, and is often associated with confusion and paradoxical undressing. Wischnewski spots are a classic manifestation of hypothermia at autopsy. Abstract : Wischnewski spots are a classic post‐mortem manifestation of accidental hypothermia. Clinical symptoms and signs of accidental hypothermia include agitation, confusion and paradoxical undressing.